Interference with Clp protease impairs carotenoid accumulation during tomato fruit ripening. (29th January 2018) - D'Andrea, Lucio; Simon-Moya, Miguel; Llorente, Briardo; Llamas, Ernesto; Marro, Mónica; Loza-Alvarez, Pablo; Li, Li; Rodriguez-Concepcion, Manuel
Abstract : The stromal Clp protease complex influences chromoplast differentiation and ensures proper carotenoid metabolism during tomato fruit ripening, probably in co-ordination with plastidial chaperones. Abstract: Profound metabolic and structural changes are required for fleshy green fruits to ripen and become colorful and tasty. In tomato ( Solanum lycopersicum ), fruit ripening involves the differentiation of chromoplasts, specialized plastids that accumulate carotenoid pigments such as β-carotene (pro-vitamin A) and lycopene. Here, we explored the role of the plastidial Clp protease in chromoplast development and carotenoid accumulation. Ripening-specific silencing of one of the subunits of the Clp proteolytic complex resulted in β-carotene-enriched fruits that appeared orange instead of red when ripe. Clp-defective fruit displayed aberrant chromoplasts and up-regulated expression of nuclear genes encoding the tomato homologs of Orange (OR) and ClpB3 chaperones, most probably to deal with misfolded and aggregated proteins that could not be degraded by the Clp protease. ClpB3 and OR chaperones protect the carotenoid biosynthetic enzymes deoxyxylulose 5-phosphate synthase and phytoene synthase, respectively, from degradation, whereas OR chaperones additionally promote chromoplast differentiation by preventing the degradation of carotenoids such as β-carotene. We conclude that the Clp protease contributes to the differentiation of chloroplasts into chromoplasts during tomato fruit ripening, acting in co-ordination with specific chaperones that alleviate protein folding stress, promote enzyme stability and accumulation, and prevent carotenoid degradation.